Percutaneous Pulmonary Valve Implantation in Small Conduits: A Multicenter Experience - Hascoet, S (2018)
BACKGROUND: Guidelines allow percutaneous pulmonary valve implantation (PPVI) in conduits above 16mm diameter. Balloon dilatation of a conduit to a diameter>110% of the original implant size is also not recommended. We analyzed patients undergoing PPVI in such conditions. METHODS AND RESULTS: Nine patients (May 2008-July 2016) from 8 institutions underwent PPVI in conduits <16mm diameter. Five patients with 16-18mm conduit diameter underwent PPVI after over-expansion of the conduit>110%. Mean age and weight of the 14 patients was 12.1 (7.7 to 16) years and 44.9 (19 to 83) kg. Median conduit diameter at PPVI was 12 (10 to 17) mm. Median systolic right ventricular pressure was 70 (40 to 94) mmHg. Procedure was successful in all cases. A confined conduit rupture occurred in 7 patients (50%) and was treated with covered stent in 6. One patient experienced dislocation of 2 pulmonary artery stents that were parked distally. The post-implantation median systolic right ventricular pressure was 36 (28 to 51) mmHg. A fistula between right-ventricle outflow and aorta was found in one patient, secondary to undiagnosed conduit rupture. This was closed surgically. After a median follow-up of 20.16 (6.95 to 103.61) months, all the patients are asymptomatic with no significant RVOT stenosis. CONCLUSIONS: PPVI is feasible in small conduits but rate of ruptures is high. Although such ruptures remain contained and can be managed with covered stents in our experience, careful selection of patients and high level of expertise are necessary. More studies are needed to better assess the risk of PPVI in this population.